SCREENING OF ALPHA-GLUCOSIDASE INHIBITORY ACTIVITY FROM TWO PRODUCTS OF THE CAPSULIZED JAMU CINNAMON EXTRACT (CINNMOMUM BURMANNII) - Febrianda, Larasati Hanifa; Jawi, I Made; Widiarthini, Ida Ayu Alit; Aman, I Gusti Made (E-Jurnal Medika Udayana, 2024)
Cinnamon ( Cinnamomim burmannii ) found in the markets, comes in many forms with one of them being a type of jamu which the cinnamon dust is capsulized. The capsulized jamu is claimed to be beneficial on treating diabetes melitus. The effects of antidiabetics on some products of the capsulized jamu is suspected to work through the alpha-glucosidase enzyme inhibition activites contained in them. The aim of this research is to verify the activities of some capsulized cinnamon dust extract in jamu ( C. burmannii ) found in the markets on its effect to inhibit alpha-glucosidase activity and to know its IC 50 value. Experiment is done by using analytic experiments using two different products (product A and product B) and by using acarbose 50mg as a positive control factor. Enzyme activity are then calculated using UV-Vis spectrophotometer on a 410 nm wavelength. The result of this research is alpha-glucosidase enzyme inhibition activity found in product A and B are 155,104 µg/mL and 6.795,893 µg/mL, wherease the acarbose as a positive control are 47,466 µg/mL. The conclusion of this research is alpha-glucosidase enzyme inhibition activity found on the products as IC 50 shows that product A has a better alpha-glucosidase enzyme inhibition activity than product B. However, when compared to the acarbose as the positive control, product A has a lesser alpha glucosidase enzyme inhibition activity. Kata kunci : Cinnamomum burmannii , diabetes mellitus, alpha glucosidase inhibition.